PELAYANAN JASA CUCI KENDARAAN BERBASIS WEBSITE - Dimas Prayuda; Febrino Mahardiva Akbar; Gabriel David Florens Ayal; Gandeva Bayu Satrya; Mia Rosmiati (INTECH, 2024)
This car washing service faces several issues, including people's laziness to visit the washing location, lack of time due to busy schedules, and often a long queue at the washing location. Cuciin website is a solution for those who have limited time to wash their dirty cars. The Cuciin website has very useful features, namely Booking and Home Service. For the Booking feature, users can view the queue at the washing location and select an available time slot to wash their cars at the location without having to wait in a long queue, hence users can come at the designated time. For the Home Service, users can request a car wash at their homes by providing the location and selecting the preferred time slot so that their cars can stay clean despite their busy schedules. Based on the questionnaire results distributed to 31 respondents, the average response was inclined towards good and very good choices.